Pengaruh Model Infiltrasi Sederhana Menggunakan Konsep Rain Garden terhadap Debit dan Kekeruhan Air Limpasan Akibat Hujan - Barid, Burhan; Lestari, Dwi (Department of Civil Engineering, Diponegoro University, 2014)
Water is the most basic requirement that is necessary for a good life on land, sea or air. Water in the face of this earth are not directly derived from the rain. All living things need water to survive. Water management should be done as quickly as possible so that its availability is maintained. Along with the development of the times and increasing daily population in Indonesia, the demand for water continues to increase. Indonesia has a tropical climate with two seasons, the dry season and the rainy season. During the dry season of drought, while in the rainy season floods. One reason is the change in land use that result in water catchment areas disappear and be replaced by buildings some hydrological model was developed to determine the water balance, such as infiltration models. Infiltration models are used to determine how much of the surface runoff or inundation (ponding) which can be infiltrated. The purpose of this study is to analyze the model's ability to absorb water in a simple infiltration runoff, infiltration simple models to analyze the influence of the flow between, to analyze the efficiency of a simple infiltration models to infiltration, and a simple model to analyze the influence of water turbidity in a state of unsaturated and saturated water. The results showed that the soil with plants media can reduce runoff and improve water quality due to rain than vacant land. Discharge runoff on bare ground while unsaturated and saturated water of 0.136 liters/sec and 0.134 liters/sec, while on the ground with the current crop of media unsaturated and saturated water at 0.1330 liters/sec and 0.1300 liters/sec. The content of the suspension on a vacant lot when unsaturated and saturated water is 6.88; 4.20; 3.94 mg/l and 2.13; 1.66; 1.11 mg/l, while in the soil with the current crop of media was saturated and saturated water is 4.40; 4.22; 2.35 mg/l and 0.92; 0.83; 0.63 mg/l.